The Limited Impact of Store Atmosphere on Customer Loyalty: Insights from Customer Satisfaction Mediation - Wesilaturrohimieh, Wesilaturrohimieh; Vania, Amelindha (Jurnal Computech & Bisnis (e-journal), 2024)
This study seeks to assess the impact of store atmosphere on customer loyalty, with customer happiness as a mediating variable. This study employs quantitative methodologies with a descriptive approach to gather questionnaire data via Google Forms. The research site encompasses five districts in Malang City: Kedungkandang, Klojen, Sukun, Blimbing, and Lowokwaru. The sample was determined via purposive sampling, with 110 respondents. The findings indicated that store atmosphere does not influence customer loyalty, while it does impact customer loyalty; additionally, customer satisfaction affects customer loyalty, and customer satisfaction mediates the relationship between store atmosphere and customer loyalty at AADK Coffee & Eatery, Tlogomas Branch, Malang City. This research has substantial significance for practitioners and scholars in marketing and customer relationship management. This study elucidates the impact of store atmosphere on customer loyalty, with customer satisfaction acting as a mediating variable, offering significant insights for enterprises, especially within the food and beverage industry. The results suggest that although store atmosphere may not directly affect consumer loyalty, it can positively increase customer satisfaction, improving loyalty. This indicates that enterprises should prioritize establishing an engaging and enjoyable retail environment to enhance consumer happiness, cultivating increased loyalty. This study enhances the existing literature by elucidating the intricate relationship between environmental characteristics and consumer views, prompting further investigation into additional mediating variables and contexts. The quantitative methodology and data gathered from several districts in Malang City augment the generalizability of the findings, providing a basis for subsequent research in analogous urban environments.